Community, Family and Work: Social participation to promote mental health and wellbeing - Upchurch, J. A. M.; OBrien, L; OBrien, L. V.; Burchell, J; Berry, H (My University, 2011)
Social participation is typically associated with better mental health, but the practical utility of this pattern is undermined by inconsistencies in the strength and direction of the relationship. It was hypothesised that the inconsistencies occur because participation in community, family and work spheres cumulatively produce different outcomes for different subpopulations in society. To identify distinct groupings of people, cluster analysis was performed using data from the Household Income and Labour Dynamics in Australia survey, and then regressions were performed to examine how different participation profiles affected wellbeing for the different groupings of people. Results showed that family structure, gender, ethnicity, age and income are relevant when grouping people to examine participation and that there are distinct relationships between participation and wellbeing for different subpopulations. Recommendations are made for health promotion strategies regarding optimal modes of social participation for different sections of Australian society.
Keywords: Health -- Mental; Social Capital; Health and wellbeing; Health; Social Capital; Mental; Health and wellbeing